1993
DOI: 10.1037/0021-9010.78.6.994
|View full text |Cite
|
Sign up to set email alerts
|

Rater training and rating accuracy: Training for dimensional accuracy versus training for ratee differentiation.

Abstract: Undergraduate subjects possessing normative or idiosyncratic rating standards were given frame-ofreference training, rater-error training, training that controlled for structural similarities between frame-of-reference training and rater-error training, or null control training. Hypothesized pretest differences that normative raters are more accurate than idiosyncratic raters were not found. However, when data were collapsed across rating aptitude, different trainings were found to improve different measures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 30 publications
4
51
0
Order By: Relevance
“…Clips were a combination of both actual third-grade classroom footage, as well as contrived second-grade classroom footage wherein students displayed varying levels of specific behaviors per researcher instructions. The use of short video clips of behavior as stimulus material was considered to be acceptable given the history of use of such an approach in prior rater training studies (e.g., LeBel et al, 2010;McIntyre, Smith, & Hassett, 1984;Stamoulis & Hauenstein, 1993;Woehr, 1994).…”
Section: Video Clipsmentioning
confidence: 99%
“…Clips were a combination of both actual third-grade classroom footage, as well as contrived second-grade classroom footage wherein students displayed varying levels of specific behaviors per researcher instructions. The use of short video clips of behavior as stimulus material was considered to be acceptable given the history of use of such an approach in prior rater training studies (e.g., LeBel et al, 2010;McIntyre, Smith, & Hassett, 1984;Stamoulis & Hauenstein, 1993;Woehr, 1994).…”
Section: Video Clipsmentioning
confidence: 99%
“…Training in behavioral assessment methods has been proposed as one way to improve the accuracy of ratings and minimize the impact of rater factors (Stamoulis & Hauenstein, 1993). However, training guidelines are seldom included or reviewed in commercially available rating scales (Floyd & Bose, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Later research found that raters who received FOR training were the most accurate in discriminating among behavioral dimensions of job performance (stereotype accuracy) and discriminating among ratees within dimensions (differential accuracy), while those who received RET were most accurate on elevation (level of ratings), and raters who received either RET or FOR training improved their ability to discriminate among ratees (Stamoulis & Hauenstein, 1993). Therefore, rater error training would be more useful when the primary goal of appraisal is to distinguish accurately among workers, while frame-of-reference training would be more useful when the primary goal of the appraisal system is to provide accurate developmental feedback to workers.…”
Section: Latham (2002)mentioning
confidence: 95%
“…measures of accuracy. Stamoulis & Hauenstein (1993) Frame-of-reference training helps distinguish Frame-of-reference and rater error training between dimensions; rater error training can be beneficial for different purposes. increases accuracy of rating favorability; both (See Table II.)…”
Section: Source Finding Applicationmentioning
confidence: 99%